Relief of expressed suicidality in schizophrenia after electroconvulsive therapy: A naturalistic cohort study. (February 2020) - Tor, Phern-Chern; Bin Abdin, Edimansyah; Hadzi-Pavlovic, Dusan; Loo, Colleen
Highlights: Electroconvulsive therapy rapid decreases expressed suicidality in treatment resistant schizophrenia. The anti-suicidal effect is mediated largely by decreases in depressive symptoms. Electroconvulsive therapy should be considered for patient resistant schizophrenia with expressed suicidality. Abstract: Suicide risk in schizophrenia is a significant treatment challenge but there are few approved treatments. Electroconvulsive therapy (ECT) is a highly effective treatment for suicidality in depression but its effect on suicidality in schizophrenia is unclear. We conducted a retrospective naturalistic study of the real-world effect of ECT on expressed suicidality as assessed by item 4 of the 24-item Brief Psychiatric Rating Scale in 113 patients with treatment resistant schizophrenia receiving ECT. 19.5% of patients expressed suicidal ideation pre-ECT of which 86.4% experienced an improvement in expressed suicidality after an average of 10.2 (SD 2.7) sessions of ECT. Changes in suicide scores before and after ECT was examined using a generalized estimating equation (GEE) model which showed that the effect of ECT on suicide was significantly mediated by depression and explained 72.2% of the decreased in expressed suicidality. ECT is effective in decreasing depression and expressed suicidality in patients with schizophrenia and should be considered as a treatment option for managing suicidality and psychosis in patients with treatment resistant schizophrenia.